2018
DOI: 10.1186/s13148-018-0529-5
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of BRCA1 and MGMT genes in white blood cells are transmitted from mothers to daughters

Abstract: BackgroundConstitutive methylation of tumor suppressor genes are associated with increased cancer risk. However, to date, the question of epimutational transmission of these genes remains unresolved. Here, we studied the potential transmission of BRCA1 and MGMT promoter methylations in mother-newborn pairs.MethodsA total of 1014 female subjects (cancer-free women, n = 268; delivering women, n = 295; newborn females, n = 302; breast cancer patients, n = 67; ovarian cancer patients, n = 82) were screened for met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…This indicated that they occurred in a single cell relatively early during the embryonic development. This model was further supported by recent studies demonstrating that the majority of constitutional BRCA1 methylation events arose early during development and seemed to remain quite stable during life and potentially were inherited from mother to daughter [12,13]. This novel hypothesis of inheritance is controversial and needs further studies to be completely elucidated [13].…”
Section: Introductionmentioning
confidence: 62%
“…This indicated that they occurred in a single cell relatively early during the embryonic development. This model was further supported by recent studies demonstrating that the majority of constitutional BRCA1 methylation events arose early during development and seemed to remain quite stable during life and potentially were inherited from mother to daughter [12,13]. This novel hypothesis of inheritance is controversial and needs further studies to be completely elucidated [13].…”
Section: Introductionmentioning
confidence: 62%
“…Although these results must be interpreted with caution as the hypermethylation levels are at the limit of detection by pyrosequencing (and thus not suitable for prediction of somatic hypermethylation), they are intriguing in the context of both possible circulating tumor DNA and findings of mosaic constitutional BRCA1 hypermethylation. Regarding the latter, mosaic constitutional BRCA1 hypermethylation has been reported in 4–7% of newborn females 40 , 41 as well as promoter methylation of BRCA1 or other cancer-related genes in peripheral blood in women who developed TNBC or high grade serous ovarian cancer 42 45 (see also Tang et al 46 for review). Unfortunately, a lack of corresponding fresh normal tissue hindered us from analyzing whether a mosaic methylation pattern was present also in non-malignant breast tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Bisulfite pyrosequencing was used for DNA methylation quantification. Five different assays (35) were used to assess the methylation status of 23 CpG sites across the BRCA1 promoter. The PCR and pyrosequencing reactions were performed using PyroMark products and reagents (Qiagen, Inc.), as previously described (36).…”
Section: Methodsmentioning
confidence: 99%